Intermittent pneumatic compression for venous thromboembolism prevention: a systematic review on factors affecting adherence - Richard Greenall; Rachel E Davis (BMJ Open)
Objective Venous thromboembolism (VTE) is a potentially fatal complication of hospitalisation. Intermittent pneumatic compression (IPC) is one approach to reducing the likelihood of a VTE. Adherence to IPC is known to be inadequate though the reasons for this remain unclear. This systematic review explores factors that affect adherence to IPC in the inpatient context.Methods Information sources—EMBASE, MEDLINE and PsycINFO were searched for literature between January 1960 and May 2019. Eligibility criteria—studies were included if they focused on inpatient care and examined factors affecting adherence to IPC devices.Results Included studies—a total of 20 out of 1476 studies were included. Synthesis of results—eight factors were identified that affected adherence: patient discomfort (n=8), healthcare professionals’ knowledge and behaviours (n=6), mobilisation (n=6), equipment supply and demand (n=3), the use of guidelines (n=3), intensive care context (n=2), computer-assisted prescribing (n=2) and patients’ knowledge of IPC (n=1).Conclusion Overall while the evidence base is quite limited, a number of factors were shown to affect adherence to IPC. These findings could be used to inform future research and quality improvement efforts to increase adherence in this very important, but currently under-researched area.